Implementation of pharmacy delivery services in the era of digital and pandemic Covid-19 - Dewi Gulyla Hari; Yasinda Oktariza; Ayu Rahmawati (Universitas Ahmad Dahlan, 2022)
The Covid-19 pandemic has had a significant impact on changes in people's behavior which currently prefer online ordering in order to implement social distancing and physical distancing. This study aims to see the behavior of pharmacy customers in using delivery services during the pandemic and strategies that can be used to attract customers to return to using delivery service. This study is an observational analytic study conducted at CV. Apotek Keluarga in the period October-December 2020. A total of 149 respondents were involved in this study. Customer behavior was observed by collecting information from customers as well as profiles of requests for delivery services from January to August 2020. Analysis of strategies to attract customer interest in shopping again at the pharmacy was carried out by looking at the correlation of the factors that influence the intention to return through distributing questionnaires. The demand profile for delivery services shows an increase in demand during pandemic in March 2020 from 22.92% to 94.35%. The results of the bivariate analysis show that there is a significant correlation on each variable score for trust, checkout satisfaction, after-delivery satisfaction, and price perception on the intention to return. The results of the multivariate analysis show that the variables, independently correlated with intention to return were trust variables with a weak positive correlation coefficient (r = 0.210), after-delivery satisfaction with sufficient positive correlation coefficient (r = 0.306), and price perception with sufficient positive correlation coefficient (0.434). Based on the results of this study, it can be concluded that the application of delivery services at pharmacies has the opportunity to be applied during the Covid-19 pandemic period as well as after the pandemic. Pharmacies need to build trust, satisfaction, and good price perceptions for customers to attract customers to return to using home delivery at pharmacies.